500 Wh kg−1 Class Li Metal Battery Enabled by a Self‐Organized Core–Shell Composite Anode. Issue 42 (15th September 2020) - Han, Bing; Xu, Dongwei; Chi, Shang‐Sen; He, Dongsheng; Zhang, Zhen; Du, Leilei; Gu, Meng; Wang, Chaoyang; Meng, Hong; Xu, Kang; Zheng, Zijian; Deng, Yonghong
Abstract: Lithium (Li) metal offers the highest projected energy density as a battery anode, however its extremely high reactivity induces dendrite growth and dead Li formation during repeated charge/discharge processes, resulting in both poor reversibility and catastrophic failure. Approaches reported to date often seek to suppress dendrites formation at the expense of energy density. Here, a strategy that resolves the above conflict and achieves a dendrite‐free and long‐term reversible Li metal anode is reported. A self‐organized core–shell composite anode, comprising an outer sheath of lithiated liquid metal (Li x LM y ) and an inner layer of Li metal, is developed, which posesses high electrical and ionic conductivity, and physically separates Li from the electrolyte. The introduction of Li x LM y not only prevents dendrite formation, but also eliminates the use of copper as an inert substrate. Full cells made of such composite anodes and commercially available LiNi0.6 Co0.2 Mn0.2 O2 (NCM622 ) cathodes deliver ultrahigh energy density of 1500 Wh L −1 and 483 Wh kg −1 . The high capacity can be maintained for more than 500 cycles, with fading rate of less than 0.05% per cycle. Pairing with LiNi0.8 Co0.1 Mn0.1 O2 (NCM811 ) further raises the energy density to 1732 Wh L −1 and 514 Wh kg −1 . Abstract : A self‐organized core–shell composite anode, which contains an outer sheath of lithiated liquid metal and an inner layer of Li metal, is reported. Benefiting from the composite anode that prevents the dendrite formation and eliminates the use of copper as substrates, full cells that pair the composite anode with a commercially available cathode deliver ultrahigh energy density exceeding 500 Wh kg −1 .